2003
DOI: 10.1038/sj.bjc.6601146
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of quality of life assessment in patients with upper gastrointestinal tract cancer

Abstract: Quality of life (QOL) is an important outcome after treatment for upper gastrointestinal tract cancer but few studies report good accrual and subsequent attrition is usually high. This study investigated the feasibility of a nurse-led service to obtain longitudinal QOL assessments and explored how clinical and sociodemographic factors influence patients' need for help to complete questionnaires. Fully informed patients were invited into the study. Baseline hospital assessments were scheduled by telephone and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Blazeby et al have studied the feasibility and implementation of these modules in patients with oesophageal cancer, and reported the short-term negative effect of oesophagectomy on quality of life scores, which returned to normal within 9 months. Improved scores were noted in patients treated with oesophagectomy compared with palliative stenting or radiotherapy 16,17,21,32 . The gastrointestinal and quality of life working groups of the EORTC have recently developed a new clinical and psychometric tool, the QLQ-OES18 33 , based on four scales and six single outcomes from the QLQ-OES24; this tool was evaluated in a recent study 25 .…”
Section: Discussionmentioning
confidence: 95%
“…Blazeby et al have studied the feasibility and implementation of these modules in patients with oesophageal cancer, and reported the short-term negative effect of oesophagectomy on quality of life scores, which returned to normal within 9 months. Improved scores were noted in patients treated with oesophagectomy compared with palliative stenting or radiotherapy 16,17,21,32 . The gastrointestinal and quality of life working groups of the EORTC have recently developed a new clinical and psychometric tool, the QLQ-OES18 33 , based on four scales and six single outcomes from the QLQ-OES24; this tool was evaluated in a recent study 25 .…”
Section: Discussionmentioning
confidence: 95%
“…Bjordal et al [22 ]found head and neck cancer patients who dropped out because of death had a much worse pretreatment EORTC QoL compared with those who filled in all questionnaires. Blazeby et al [31 ]also observed that patients with advanced disease, receiving palliative treatment, or with poor performance status usually had poorer follow-up QoL questionnaire compliance. Besides being an outcome measure to compare treatments in clinical trials, significant differences in QoL scores were also found to be predictive of survival in cancer patients [32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, since mortality and complications associated with surgery have been reduced and the number of stomach cancer survivors is increasing [6,7], more attention should be directed to postoperative morbidity and quality of life (QOL) [1,[6][7][8][9]]. An added benefit of QOL assessments is that they facilitate communication between doctors and patients [10].…”
Section: Introductionmentioning
confidence: 99%